2011
DOI: 10.1016/j.amjcard.2011.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Usefulness of Cardiac Resynchronization Therapy in Three Age-Groups (<65, 65-74 and ≥75 Years) (from the InSync/InSync ICD Italian Registry)

Abstract: Chronic heart failure is one of the most important geriatric syndromes, associated with disability, increased hospital admissions, and high mortality. The aim of this study was to evaluate the existence of age-related differences in clinical effectiveness and outcomes of cardiac resynchronization therapy (CRT), alone or in combination with an implantable cardioverter-defibrillator (CRT-D), in a large, real-world registry. A total of 1,787 patients admitted for CRT or CRT-D to the 117 centers participating in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
2
15
0
9
Order By: Relevance
“…25 Similarly, the subanalysis of the InSync/InSync ICD Italian Registry demonstrated significant reductions in LV volumes at 6-and 12-month follow-up independent of age. 12 In line with these observations, subanalysis of the Multicenter Automatic Defibrillator Implantation Trial with Cardiac Resynchronization Therapy (MADIT-CRT) comparing the magnitude of LVESV change at 12-month follow-up among patients <60, 60 to 74, and ≥75 years reported no significant differences between age groups. 13 The present results provide more evidence on the beneficial effects of CRT on LV structure and function and would support the appropriateness of implanting CRT in old patients with heart failure.…”
Section: Effect Of Age On LV Reverse Remodeling After Crtmentioning
confidence: 54%
See 3 more Smart Citations
“…25 Similarly, the subanalysis of the InSync/InSync ICD Italian Registry demonstrated significant reductions in LV volumes at 6-and 12-month follow-up independent of age. 12 In line with these observations, subanalysis of the Multicenter Automatic Defibrillator Implantation Trial with Cardiac Resynchronization Therapy (MADIT-CRT) comparing the magnitude of LVESV change at 12-month follow-up among patients <60, 60 to 74, and ≥75 years reported no significant differences between age groups. 13 The present results provide more evidence on the beneficial effects of CRT on LV structure and function and would support the appropriateness of implanting CRT in old patients with heart failure.…”
Section: Effect Of Age On LV Reverse Remodeling After Crtmentioning
confidence: 54%
“…An age-related increase in noncardiac mortality was also reported in the InSync ICD Italian Registry. 12 In addition, we evaluated 2 important end points for the elderly population. First, our study showed an equal proportional incidence of heart failure hospitalizations combined with all-cause mortality between the age groups, suggesting a comparable effect of CRT on clinical symptoms and quality of life.…”
Section: Device-related Adverse Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elderly patients respond just as well as younger patients do with CRT. A recently published article examining an Italian ICD registry divided patients into 3 age-groups (age\65, 65-75 and[75 years) and found no differences between the groups in terms of responding to CRT [77]. There was, however, an increase in all-cause mortality in the [75 group.…”
Section: Clinical Managementmentioning
confidence: 96%